Lattice Boltzmann Simulation of Droplet Generation in a Microfluidic Cross-Junction (Communications in Computational Physics, 2020)
Using the lattice Boltzmann multiphase model, numerical simulations havebeen performed to understand the dynamics of droplet formation in a microfluidiccross-junction. The influence of capillary number, flow rate ratio, viscosity ratio, andviscosity of the continuous phase on droplet formation has been systematically studiedover a wide range of capillary numbers. Two different regimes, namely the squeezing-likeregime and the dripping regime, are clearly identified with the transition occurringat a critical capillary number Cacr. Generally, large flow rate ratio is expected toproduce big droplets, while increasing capillary number will reduce droplet size. Inthe squeezing-like regime (Ca ≤ Cacr), droplet breakup process is dominated by thesqueezing pressure and the viscous force; while in the dripping regime (Ca > Cacr),the viscous force is dominant and the droplet size becomes independent of the flowrate ratio as the capillary number increases. In addition, the droplet size weakly dependson the viscosity ratio in both regimes and decreases when the viscosity of thecontinuous phase increases. Finally, a scaling law is established to predict the dropletsize.